The Urgency of Reformulating Criminal Offences on the Misuse of Personal Data in Indonesia’s Crypto Asset Ecosystem - Dian Eka Kusuma Wardani; Amir Amir; Muh. Iqbal (Yayasan Vifada Cendikia Indonesia, 2025)
Purpose: This study examines the urgency of reformulating criminal offences for the misuse of personal data within Indonesia’s crypto-asset ecosystem, based on the hypothesis that current offence design is not commensurate with the level of risk and complexity of crypto data-processing practices. Research Design and Methodology: Using a normative legal method with a doctrinal design, this research is supported by conceptual, comparative, and analytical approaches to national legislation, data-protection and crypto-asset regimes in several countries, and relevant scholarly literature and institutional reports. Findings and Discussion: The study finds that although the Personal Data Protection Law, the Electronic Information and Transactions Law, and sectoral crypto-asset regulations provide a basis for criminalisation, existing offence constructions remain general, fragmented, and insufficiently responsive to the technological and institutional characteristics of the crypto ecosystem. Implications: The study proposes a sector-specific model of criminalisation that clearly articulates the protected legal interests, liable subjects, prohibited conducts, and standards of corporate criminal liability, and offers a conceptual foundation for legislative reform while inviting further mixed normative–empirical research on its operationalisation.